ANALISA PENGATURAN PERLINDUNGAN UPAH BERDASARKAN PERATURAN PERUNDANG-UNDANGAN DAN PRINSIP-PRINSIP HUKUM - Wati, Yetni (Alhurriyah, 2017)
The setting of wage protection in the positive law in Indonesia is still not perfect to provide legal certainty for the weaker party melindungan social economy, every anniversary of May Day is always the union demanded political abolish the wage cost, PP.No. 78 of 2015 pro on the interests of investors ask revoked. The principle of legal certainty in the norm of wage protection needs to be realized with respect to: the concept of the protection of wages, lack of certainty purpose of law, established by the competent authorities, the law can be accepted by society, their legal materials in accordance with the legal hierarchy, the company's obligation to make books wages, legal language which was unambiguous in its legal norms.